The Use of Environmentally Friendly Technologies in the Construction of Road Surfaces, with the Aim of the Rational Distribution of Natural Resources in Russia - Elena Chernykh (Polish Society of Ecological Engineering (PTIE), 2021)
The subject of research in this article is recycled plastics as a leading component in pavement construction. The aim of the work was to evaluate innovative methods of using nature-saving technologies in the construction of road surfaces, with the aim of rational distribution of natural resources. The advantages of asphalt pavement are cost-effectiveness, recycling, ease of maintenance, the ability to lay asphalt on the old layer, and good adhesion. Production of asphalt with the addition of plastic is 3% more expensive than usual, but its environmental friendliness and prospects fully compensate for the increased production costs.